Prediction of family self-esteem and academic self-esteem based on neuroticism and conscientiousness - Talaeizadeh, Forough (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2019)
Introduction: The objective of this study was to predict familyself-esteem and academic self-esteem based on neuroticismand conscientiousness.Method: This study was a correlational - descriptive study. Theresearch population included all second-grade high school studentsin Shiraz, Iran, in the academic year of 2018-2019.Result: Using multi-stage cluster sampling, 250 students(125 females and 125 males) were selected and evaluatedusing the NEO Personality Inventory and Coopersmith SelfesteemInventory.Conclusion: The results of the multivariate regression analysisshowed that neuroticism negatively predicted the familyself-esteem and academic self-esteem. Moreover, conscientiousnesswas able to positively predict family self-esteemand academic self-esteem